Sustainability of community media: proposal for a multidimensional model - de la Noval Bautista, Luis Alain; Barranquero Carretero, Alejandro; García-Caballero, Sara (Estudios sobre el Mensaje Periodístico, 2024)
This article presents and supports a projective model to assess the sustainability of community media based on the articulation of a set of political, structural-organizational, legal, economic, socio-cultural, ecological, technological and communicational dimensions. These are operationalized and interrelated to optimize the processes of organization, management, production, access, use and appropriation of these media, committed to citizenship, for an effective exercise of the rights to information and communication, after which premises are offered to adapt the model to different contexts. It is not only about the capacity to remain in time, but also that the communicational proposal is capable of generating processes of transformation and ecological-social justice. The research that supports this model is of a communicological, empirical and applied nature, as well as employing a qualitative methodological perspective. The research techniques used were literature review, documentary analysis and validation of the model by specialists through the Delphi method in two rounds. As part of the model, a set of guiding principles is proposed, as well as a system of qualitative and quantitative indicators, on a scale of 0 to 100 points, which allow the evaluation of each of the dimensions mentioned above. Finally, a strategic plan is drawn up to enable decisions to be taken to maintain or increase the level of sustainability of the community environment. Among its main values, the model designed is holistic, dynamic and open to flexible application by the organizations that manage these environments.